Analisis Break Even Point Multi Produk Penjualan Keripik Pada Usaha Aulia Food Luwuk Banggai: Break Even Point Analysis of Multi-Product Chip Sales at Aulia Food Luwuk Banggai Business - Sibay, Yusnita Fitarini; Tandiawan, Vira (Fakultas Ekonomi, Universitas Tompotika Luwuk, 2026)
The objective of this research is to determine the minimum sales level for Aulia Food Luwuk Banggai required to achieve the Break Even Point (BEP) for its multiproduct sales, thus avoiding losses. Aulia Food, an SME, produces eight variants of chips, including taro, sweet potato, and cassava chips, but has only relied on historical sales data for profit planning, without implementing multi-product BEP analysis. This study utilized quantitative analysis with the Break Even Point Multi Product method based on Aulia Food's 2024 sales data. The major finding shows that the multi-product BEP for 2024 is achieved at a minimum sales level of Rp370,000,000. The BEP in units for the variants are: Taro Chips Balado/Spicy Sweet at 3,166 units each, Sweet Potato Chips Original/Balado at 3,124 units each, Cassava Chips Balado/Grilled Corn at 3,166 units each, and Banana Chips Brown Sugar/Sweet at 3,108 units each. Since the company’s 2024 sales were above the BEP level, a profit was generated. The high Contribution Margin indicates the company's ability to cover fixed costs and its potential for future profit. For the 2025 period, the business plans a profit of Rp1,935,644,000.